Tracking CAADP indicators and processes [In the 2016 ATOR] - Makombe, Tsitsi; Tefera, Wondwosen; Matchaya, Greenwell C.; Benin, Samuel (International Food Policy Research Institute, 2017)
Chapter 11 tracks progress on CAADP indicators outlined in the CAADP Results Framework for 2015–2025 in the areas of economic growth, food and nutrition security, employment, poverty, agricultural production and productivity, intra-African trade and market performance, and public agriculture-sector expenditure. It also reviews countries’ progress in the CAADP implementation process and in strengthening systemic capacity to deliver results.